2012
DOI: 10.1002/ejic.201200185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structure, Morphology, and Luminescence Properties in Blue‐Red Emitter, Europium‐Activated ZnAl2O4 Nanospinels

Abstract: A sol-gel method was employed for the preparation of a series of europium-doped ZnAl 2 O 4 nanoparticles. The samples were calcined in the 700 to 1400°C range for 3 h. The impact of calcination temperature on the structural and luminescence properties of the obtained nanomaterials was studied with X-ray diffraction (XRD), transmission electron microscopy (TEM), and photoluminescence measurements. XRD analyses demonstrated the powders to be single-phase spinel nanopowders. The average particle size varied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Spinel‐type compounds, described by the general chemical formula AB 2 O 4 (where A is a cation in the +2 oxidation state and B is a cation in the +3 state), have attracted significant attention because of their excellent magnetic performance,1 high melting points,2 resistance to aggressive chemicals, wide band gap,3 electrical conductivity,4 and luminescence 5,6. Among the many spinel representatives, those of the type ZnX 2 O 4 (X = Al 3+ , Ga 3+ , In 3+ ) are very promising candidates in aerospace‐related applications, where they serve as reflective optical coatings,7 transparent conducting oxide (TCO) materials,8,9 and phosphor host materials (after proper activation with optically active ions) for flat panel displays (FPDs),10 field emission displays (FEDs),11 or vacuum fluorescent displays (VFDs) 12.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel‐type compounds, described by the general chemical formula AB 2 O 4 (where A is a cation in the +2 oxidation state and B is a cation in the +3 state), have attracted significant attention because of their excellent magnetic performance,1 high melting points,2 resistance to aggressive chemicals, wide band gap,3 electrical conductivity,4 and luminescence 5,6. Among the many spinel representatives, those of the type ZnX 2 O 4 (X = Al 3+ , Ga 3+ , In 3+ ) are very promising candidates in aerospace‐related applications, where they serve as reflective optical coatings,7 transparent conducting oxide (TCO) materials,8,9 and phosphor host materials (after proper activation with optically active ions) for flat panel displays (FPDs),10 field emission displays (FEDs),11 or vacuum fluorescent displays (VFDs) 12.…”
Section: Introductionmentioning
confidence: 99%
“…10 and 11 present the emission spectra of Ca 10 (PO 4 ) 6 Cl 2 :Eu 3+ samples collected at 300 K and 77 K upon excitation at 266 nm as a function of Eu 3+ ions concentration (1-5% mol) corrected accordingly to the apparatus response. The discussion of Eu 3+ ions luminescent behavior already found a special place in the scientific literature since it can be indicative of structural disorders, 28,29 phase transtions 30 and of course finds application as a phosphor material, 31 Typically emission spectra of the Eu 3+ consist of characteristic bands in the visible region ascribed to the specific electron transitions occurring within the f-f shell of Eu 3+ ions. In most cases, the 5 D 0 → 7 F 0−4 transitions are observed as a result of the depopulation of the lowest lying meta-stable excited 5 D 0 level to the respective crystal field components of the 7 F 0−4 levels of the 7 F ground term.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In accordance to literature, it is suggested that the existence of Eu 2+ ions could play an important role in the reduction of silver ions as well as a photoluminescence. A spontaneous reduction phenomenon of Eu 3+ to Eu 2+ was demonstrated under air condition 23,24,25 . In this case, the influence of Eu 2+ ions on the Ag + ions was studied.…”
Section: Antibacterial Activity Of Ca 10 (Po 4 ) 6 CL 2 Nanoparticlesmentioning
confidence: 95%